2016
DOI: 10.1589/jpts.28.701
|View full text |Cite
|
Sign up to set email alerts
|

Radial extracorporeal shock wave therapy for heterotopic ossification

Abstract: [Purpose] To report the effects of radial extracorporeal shock wave therapy (RSWT) on heterotopic ossification (HO). [Subjects and Methods] Two cases of neurogenic HO in the upper extremity were administered RSWT using the MASTER PLUS® MP 2000 (Storz, Tägerwilen, Switzerland) and ultrasonographic guidance. The RSWT protocol consisted of 3,000 pulses at a frequency of 12 Hz during each treatment. The intensity level ranged from 2–5 bars, and it was administered 5 times a week for 4 weeks, a total of 20 treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…ESWT is widely applied to patients with various musculoskeletal diseases 11 ) , and Lee and Han 12 ) reported that it is an effective treatment for reducing patients’ pain and improving their function. Wang et al 13 ) reported extracorporeal shock waves were effective in preventing and treating knee arthritis in rats with knee arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…ESWT is widely applied to patients with various musculoskeletal diseases 11 ) , and Lee and Han 12 ) reported that it is an effective treatment for reducing patients’ pain and improving their function. Wang et al 13 ) reported extracorporeal shock waves were effective in preventing and treating knee arthritis in rats with knee arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The applied ESWT protocol also varied greatly, with 3000 to 4000 shocks applied at frequencies ranging from 3 to 12 Hz and intensities distributed from 1 to 5 bars. [5,[8][9][10][11][17][18][19] In this case, the setting of the ESWT was established by referring to the frequency and intensity in the study of the ESWT protocol in the previous study by Li et al, in which there was an actual change in the size of HO on radiological findings. In the study of Li et al, 4000 shocks were applied to the unilateral hip with HO at 8 Hz and energy of 1 bar.…”
Section: Mechanisms Of Eswt For the Treatment Of Ho: Previous Studies...mentioning
confidence: 99%
“…[7] Few studies have applied ESWT for the treatment of HO, and the results have indicated that ESWT was effective in reducing patients' pain or improving ROM and quality of life. [5,[8][9][10][11] However, almost none of the studies reported degradation in the size of HO on images obtained before and after ESWT application. Here, we present a case of a 36-yearold male patient with pontine hemorrhage who had severe neurogenic HO on both hip joints.…”
Section: Introductionmentioning
confidence: 99%
“…It leads to the loss of flexibility and difficulties with the activities of daily living (ADLs) due to chronic inflammation accompanied by intra-articular fibrosis 2 ) . While the methods for treating adhesive capsulitis include thermotherapy, cryotherapy, electrotherapy, exercise therapy, and manual therapy 3 ) , extracorporeal shock wave therapy (ESWT) has recently drawn great attention as a non-surgical treatment method 4 ) . This therapy assists revascularization through the application of extracorporeal shock waves to the lesion, and reduces pain and improves function in the shoulder by stimulating or reactivating the healing process of connective tissues, including tendons and bones 5 ) .…”
Section: Introductionmentioning
confidence: 99%